2020
DOI: 10.3390/ijerph17103356
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Capacity of Air Travel Patterns during the Global Spread of the COVID-19 Pandemic: Risk, Uncertainty and Randomness

Abstract: Air travel has a decisive role in the spread of infectious diseases at the global level. We present a methodology applied during the early stages of the COVID-19 pandemic that uses detailed aviation data at the final destination level in order to measure the risk of the disease spreading outside China. The approach proved to be successful in terms of identifying countries with a high risk of infected travellers and as a tool to monitor the evolution of the pandemic in different countries. The high number of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 34 publications
3
80
0
4
Order By: Relevance
“…The response options are: 3 = nearly every day, 2 = more than half the days, 1 = several days, and 0 = not at all for PHQ-9 and GAD-7; 4 = always, 3 = often, 2 = sometimes, 1 = rare, and 0 = never for ISI-7 and IES-7. The total scores of these survey scales are interpreted as follows: PHQ-9, extremely severe (22-28), severe (15)(16)(17)(18)(19)(20)(21), moderate (10)(11)(12)(13)(14), mild (5)(6)(7)(8)(9), and normal (0-4) depression; GAD-7, severe (15)(16)(17)(18)(19)(20)(21), moderate (10)(11)(12)(13)(14), mild (5)(6)(7)(8)(9), and normal (0-4) anxiety; ISI-7, severe (22-28), moderate (15)(16)(17)(18)(19)(20)(21), subthreshold (8)(9)(10)(11)(12)(13)…”
Section: Mental Health Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The response options are: 3 = nearly every day, 2 = more than half the days, 1 = several days, and 0 = not at all for PHQ-9 and GAD-7; 4 = always, 3 = often, 2 = sometimes, 1 = rare, and 0 = never for ISI-7 and IES-7. The total scores of these survey scales are interpreted as follows: PHQ-9, extremely severe (22-28), severe (15)(16)(17)(18)(19)(20)(21), moderate (10)(11)(12)(13)(14), mild (5)(6)(7)(8)(9), and normal (0-4) depression; GAD-7, severe (15)(16)(17)(18)(19)(20)(21), moderate (10)(11)(12)(13)(14), mild (5)(6)(7)(8)(9), and normal (0-4) anxiety; ISI-7, severe (22-28), moderate (15)(16)(17)(18)(19)(20)(21), subthreshold (8)(9)(10)(11)(12)(13)…”
Section: Mental Health Problemsmentioning
confidence: 99%
“…Studies proved that COVID-19 has caused a high prevalence of mental health problems in China [ 8 , 9 , 10 , 11 , 12 ] and other countries around the world [ 13 , 14 , 15 , 16 ]. Some researchers have attempted to understand the outbreak of this novel coronavirus from a global health perspective [ 17 , 18 , 19 ]. However, most studies focused on the psychological effects of people who were infected with COVID-19, medical workers, or people in specific regions [ 10 , 11 , 12 , 13 , 14 , 15 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies investigate the following, important question: How does air transportation (and other modes) contribute to the spread of COVID-19 ( Christidis and Christodoulou, 2020 ; Gilbert and et al, 2020 ; Zhang et al, 2020 )? In this study, we investigate a complementary question: What is the impact of the COVID-19 pandemic on global aviation from a complex system perspective?…”
Section: Introductionmentioning
confidence: 99%
“…Among these reviewed articles, 15% (n=12) worked on a global or multi-national scale. The global studies are more focused on mobility and how COVID-19 transmitted via airports and other human mobility [17][18][19] .…”
Section: Summary and Characteristics Of Reviewed Articlesmentioning
confidence: 99%
“…A total of nine articles were identified that emphasized on identifying the spatial transmission pattern analysis of COVID-19 15,16,19,[62][63][64][65][66][67] . So far, only one study had used geospatial analysis to identify Spatio-temporal clusters and prediction modeling for COVID-19 transmission.…”
Section: Spatial Pattern Analysis Of Covid-19mentioning
confidence: 99%